Maize Growth and Yield Response to a Biostimulant Amendment. Issue 6 (1st November 2016) - Francis, Paul B.; Earnest, Larry D.; Bryant, Kelly
ABSTRACT: Various companies are marketing biostimulant products with claims of higher yields and improved quality. Greenhouse and field experiments were conducted from 2010–2013 to determine the influence of Foliar Blend ® (FB, Agri-Gro Marketing, Inc., Doniphan, MO), a chelated micronutrient/biostimulant amendment, on the growth and seed yield of maize ( Zea mays L.). When applied pre-emergence and again at V5 growth, greenhouse-grown maize seedling heights and leaf area increased at 2.34 L FB/ha or greater and root and shoot dry matter increased at 7 L FB/ha compared with untreated plants. In field studies, maize yields increased at 2.34 L FB/ha or greater in 2011. In 2012, yields improved with FB but not significantly. Primary ear heights at 1.2 L FB/ha and 2.34 L FB/ha were greater than the control in 2011 but not in 2012. We conclude that FB can alter maize growth, but yield responses are inconsistent and possibly related to environmental interactions.